(untitled) (CAHIERS MAGELLANES-NS, 2024)
The notion that all human feelings, thoughts, and actions—even consciousness itself—are simply the byproducts of neuronal activity in the brain is known as the astounding hypothesis, according to Nobel laureate Francis Crick. The promise of this theory for marketers is that it can lessen the ambiguity and guesswork that have previously hampered efforts to understand consumer behaviour. In order to forecast and possibly even influence consumer behaviour and decision-making, the field of neuromarketing, also referred to as consumer neuroscience, analyses the brain. Neuromarketing, which was up until recently thought of as an extravagant "frontier science," has been strengthened over the recent five years by a number of ground-breaking research that show it has the ability to benefit marketers. The term "neuromarketing" is used colloquially to describe the measurement of physiological and neural signals to obtain knowledge of customers' underlying motives, desires, and choices. This information can then be used to inform product development, pricing, and other marketing areas as well as creative advertising. The two most popular techniques for measuring are brain scanning, that analyzes neural activity, and physiological tracking, which monitors eye movement and other proxies for that activity. Neuromarketing (NM) involves the use of neuroimaging and physiological tools to document the neural correlates of consumers' behaviour toward different types of marketing stimuli such as brands and advertisements. The purpose of this study is to present the current tools used in empirical research over the last 16 years. To select empirical and review papers that used NM tools in the last five years, we used the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) framework and a bibliometric analysis. To answer our research questions, we extracted and analysed twenty-four documents from the Scopus and WOS database. In order to be able to understand the evolution of neuro marketing, analysing the progress, the fields of progress and the relevant advantages of the same in the marketing domain will be the problems we are looking at in this study.